2020 IEEE International Conference on Multimedia and Expo (ICME) 2020
DOI: 10.1109/icme46284.2020.9102912
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing VVC Through Cnn-Based Post-Processing

Abstract: This paper presents a new Convolutional Neural Network (CNN) based post-processing approach for video compression, which is applied at the decoder to improve the reconstruction quality. This method has been integrated with the Versatile Video Coding Test Model (VTM) 4.01, and evaluated using the Random Access (RA) configuration using the Joint Video Exploration Team (JVET) Common Test Conditions (CTC). The results show coding gains on all tested sequences at various spatial resolutions over different quantisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 23 publications
(39 reference statements)
0
16
0
Order By: Relevance
“…Postprocessing is commonly applied at the video decoder, on the reconstructed frames, to reduce various coding artefacts and enhance visual quality. Here, we employed the CNN-based postprocessing method proposed by Zhang et al [16], which has been reported to offer significant coding gains over VVC. Its network architecture was modified based on the generator (SRResNet) of SRGAN [50].…”
Section: Postprocessing Methods With Image Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…Postprocessing is commonly applied at the video decoder, on the reconstructed frames, to reduce various coding artefacts and enhance visual quality. Here, we employed the CNN-based postprocessing method proposed by Zhang et al [16], which has been reported to offer significant coding gains over VVC. Its network architecture was modified based on the generator (SRResNet) of SRGAN [50].…”
Section: Postprocessing Methods With Image Enhancementmentioning
confidence: 99%
“…In heavy compression, quantization filters out the noise [12]. CNN-based methods are also popular for postprocessing and can provide significant image enhancement, leading to better final ratedistortion performance with significantly lower complexity [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Filtering in the decoder side [32], [54], [55] can also solve the problem of repeated enhancement well. For example, DS-CNN was designed by Yao et al [32] to achieve quality enhancement as well.…”
Section: Related Workmentioning
confidence: 99%
“…Li et al [54] adopted a 20-layers deep CNN to improve the filtering performance. Zhang et al [55] proposed a post-processing network for VTM 4.0.1. In summary, filtering in inter frames is more challenging than that of intra frames.…”
Section: Related Workmentioning
confidence: 99%
“…This paper is a comprehensive extension of our previous work [3], which solely focused on the PSNR driven optimization of VVC compressed content. The primary differences are summarized below:…”
Section: Introductionmentioning
confidence: 99%